Media Sosial sebagai Strategi Peningkatan Ekonomi bagi Bisnis Kerajinan Eceng Gondok "Witrove" di Surabaya - Suksmawati, Herlina (Jurnal Bisnis Indonesia, 2024)
Water hyacinth is a weed in waters, but this weed will be profitable if used as raw material for crafts,and touched with art and creative ideas. The results of processing water hyacinth plants can becreated into products that have functions or benefits. These natural materials can be used as rawmaterials for crafts which have high artistic and economic value. Making various water hyacinthcrafts can be developed into a commercial craft industry. The necessary materials and equipment areeasy to obtain or purchased at low prices. The manufacturing process is also quite easy, it can bedone by both male and female workers. Water hyacinth can be combined with other materials to formcraft products that are more varied, luxurious and elegant. Apart from that, water hyacinth crafts areeasy to market, and even have the potential to be marketed as export commodities to variouscountries. In line with the rapid development of the handicraft market, the partner group wishes todevelop creativity and innovate to develop products made from water hyacinth so that they are moreattractive to the market and have selling value. The marketing carried out by handicraft craftsmen inWitrove Surabaya still uses traditional marketing models, which only depend on the place where thecraftsmen exhibit their products. To increase income, in this case assistance is needed in marketingusing social media.Keywords: Water Hyacinth; Social Media; @Witrove